2000
DOI: 10.1175/1520-0485(2000)030<2035:tdoapm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of a Partially Mixed Estuary*

Abstract: Measurements of velocity, density, and pressure gradient in the lower Hudson River estuary were used to quantify the dominant terms in the momentum equation and to characterize their variations at tidal and springneap timescales. The vertical momentum flux (assumed to be due mainly to turbulent shear stress) was estimated indirectly, based on the residual from the acceleration and pressure gradient terms. The indirect estimates of stress compared favorably to bottom stress estimates using a quadratic drag law,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
185
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 24 publications
23
185
4
1
Order By: Relevance
“…In these estuaries, the stratification varies within a broad range of values between ebb and flood conditions with often very weak stratification during strongest tidal flow (e.g. Nepf and Geyer, 1996;Peters, 1997;Geyer et al, 2000;Kay, 2003). The LSLE does not behave such as these estuaries since even in the near bottom part of the water column the stratification remains nearly constant between the ebb and flood (Fig.…”
Section: Boundary Mixing In the Lslementioning
confidence: 93%
See 1 more Smart Citation
“…In these estuaries, the stratification varies within a broad range of values between ebb and flood conditions with often very weak stratification during strongest tidal flow (e.g. Nepf and Geyer, 1996;Peters, 1997;Geyer et al, 2000;Kay, 2003). The LSLE does not behave such as these estuaries since even in the near bottom part of the water column the stratification remains nearly constant between the ebb and flood (Fig.…”
Section: Boundary Mixing In the Lslementioning
confidence: 93%
“…For certain shallow highly stratified or partially mixed estuaries, one may expect that most of the dissipation is determined by bottom stress and stress in the pycnocline (e.g. Geyer and Smith, 1987;Geyer et al, 2000Geyer et al, , 2010. In these estuaries, the stratification varies within a broad range of values between ebb and flood conditions with often very weak stratification during strongest tidal flow (e.g.…”
Section: Boundary Mixing In the Lslementioning
confidence: 99%
“…[41] For the ebb data, the vertical spreading of the dye patch provides a more reliable estimate of the vertical mixing rate, because the vertical mixing rate is expected to be more uniform through the water column during the ebb [Peters and Bokhorst, 2000;Geyer et al, 2000]. Also, the entrainment model of Chant et al [2007] was not applicable to the more vertically continuous vertical gradients observed during the ebb.…”
Section: Along-estuary Dispersion 421 Vertical Shear Dispersionmentioning
confidence: 99%
“…Interestingly, these processes tend to vary inversely with each other. As tidal amplitude increases, the mixing increases, and the strength of the estuarine exchange flow decreases (Geyer and Cannon, 1982;Geyer et al, 2000), thus potentially increasing the residence time. Conversely, stronger tidal velocities cause greater horizontal dispersion which can decrease residence time (Zimmerman, 1986).…”
Section: Introductionmentioning
confidence: 99%